PENGEMBANGAN EKONOMI MASYARAKAT MELALUI PEMANFAATAN SUMBER EKONOMI UMAT - Nur Alhidayatillah Alhidayatillah; Esti Alfiah (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2017)
The economic problems that befell Muslims today are due to our dependence on the capitalist and socialist world economic system. Muslims are in a grip too strong and hard to break away. All sides of the economy are controlled and operated by a capitalist system that does not care about the values to be considered. The capitalist economy justifies all means of getting everything. Capitalism focuses only on income and profit. This condition creates a huge gap in society